Longitudinal Survey of Fungi in the Human Gut: ITS Profiling, Phenotyping, and Colonization - Raimondi, Stefano; Amaretti, Alberto; Gozzoli, Caterina; Simone, Marta; Righini, Lucia; Candeliere, Francesco; Brun, Paola; Ardizzoni, Andrea; Colombari, Bruna; Paulone, Simona; Castagliuolo, Ignazio; Cavalieri, Duccio; et al. (Frontiers in Microbiology, 2019)
The fungal component of the intestinal microbiota of eight healthy subjects was studied over 12 months using metagenome survey and culture-based approaches. Aspergillus, Candida, Debaryomyces, Malassezia, Penicillium, Pichia, and Saccharomyces were the most recurrent and/or dominant fungal genera, according to metagenomic analysis. The biodiversity of fungal communities was lower and characterized by greater unevenness, when compared to bacterial microbiome. The dissimilarities both among subjects and over the time within the same subject suggested that most of the fungi passed through the gastro-intestinal tract (GIT) without becoming stable colonizers. Certain genera, such as Aspergillus and Penicillium, were isolated in a minority of cases, although they recurred abundantly and frequently in the metagenomics survey, likely being environmental or food-borne fungi that do not inhabit the GIT. Candida genus was recurrently detected. Candida albicans isolates dominated among the cultivable mycobiota and longitudinally persisted, likely as commensals inhabiting the intestine or regularly reaching it from Candida-colonized districts, such as the oral cavity. Other putative colonizers belonged to C. zeylanoides, G. candidum, and R. mucilaginosa, with persisting biotypes being identified. Phenotyping of fungal isolates indicated that C. albicans adhered to human epithelial cells more efficiently and produced greater amounts of biofilm in vitro than non-albicans Candida (NAC) and non-Candida fungi (NCF). The C. albicans isolates also induced the highest release of HBD-2 by human epithelial cells, further differing from NAC and NCF. Nine representative isolates were administered to mice to evaluate the ability to colonize the intestine. Only two out of three C. albicans strains persisted in stools of animals two weeks after the end of the oral administration, whereas NAC and NCF did not. These results confirm the allochthonous nature of most the intestinal fungi, while C. albicans appears to be commonly involved in stable colonization. A combination of specific genetic features in the microbe and in the host likely allow colonization from fungi normally present solely as passengers. It remains to be established if other species identified as potential colonizers, in addition to Candida, are true inhabitants of the GIT or rather reach the intestine spreading from other body districts.